An interdisciplinary realist take on moral agency. Issue 2 (15th March 2023) - Li, Li
ABSTRACT: This paper reports an empirical study on moral reasoning. It seeks to answer two questions: in the moral framing of tourism matters, what does this reasoning consist of? How are these elements mobilized by actors to reach moral pronouncement(s)? Through the means of group interviews, abduction and retroduction, this study finds that moral muteness (i.e. silence to socially unacceptable conduct) seems to be the moral pronouncement that the participants are likely to conduct in a condition whereby the social and cultural systems being perceived insufficient to protect individuals who pursue a righteous action. The analysis reveals that (1) moral template, reflexivity, self-efficacy and emotions are constitutive elements of moral agency; (2) these agential properties permit the emergence of four moral reasoning processes, which explain moral muteness.